THE EFFECT OF GARLIC (Allium sativum) EXTRACT ON THE HISTOPATOLOGICAL LUNG OF BALB/C MICE WITH NICOTINE EXPOSURE - Ardiansyah Mahardika; Desy Armalina; Ratna Damma Purnawati; Hermawan Istiadi; Akhmad Ismail (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2022)
Abstract Background: Nicotine is a major aspect of smoking. Nicotine cause damage to the lungs because the oxidative stress caused triggers an inflammatory response and lung damage to the alveoli. Garlic extract as an antioxidant agent so that it can against oxidative stress caused by nicotine exposure.Objective: This study is to proving the effect of multilevel dose of garlic extract on lung histopathology of BALB/c mice exposed to nicotine by inhalationMethods: The study used an experimental post test only control group design which was carried out for 24 days. Mice were given an adaptation period of 7 days followed by a treatment period of 14 days. On the last day, the lungs will be terminated and taken for histopathological tests. Mice were divided into 4 groups, namely a Healthy Control Group that was only given standard feed, a Negative Control Group that was given exposure to nicotine by inhalation at a dose of 10 mg/KgBW, treatment group 1 was given garlic extract 300 mg/KgBW orally and exposed to nicotine inhalation with a dose of 10 mg/KgBW, and treatment group 2 who were given garlic extract 500 mg/KgBW orally and exposed to nicotine by inhalation at a dose of 10 mg/KgBW. Histopathological preparations were made on each sample with Hematoxylin-Eosin paint which was then observed microscopically and assessed for severity of damage using scoring criteria.Results: Based on microscopic observations, the degree of lung damage is grouped into normal, mild, moderate, and severe degrees. The results in each group are in the following groups: Healthy Control Group : 73%,27%,0%,0% ; C(-) :0%,0%,33%,67% ; T1 : 0%,33%,67%,0% ; T2 : 0%,100%,0%,0%. The Kruskal Wallis test was performed to obtain significant differences, followed by the Mann Whitnney test which compared the treatment groups which showed significant results.Conclusion: By Giving garlic extract can reduce the degree of microscopic damage of mice lung due to nicotin inhalation exposure.